Homology Modeling and Molecular Docking of the Leishmania Protein Kinase, E9BJT5, A New Target for Leishmaniasis Therapeutics - Niloofar Lari; Razieh Jalal; Majid Rajabian Noghuondar; Zarrin Minuchehr (Fasa University of Medical Sciences, 2020)
Background & Objective: Leishmaniasis is taken into account as a parasitic disease caused by the Leishmania genus. A major challenge of the leishmaniasis is associated with the occurrence of treatment failure after drug treatment. Target identification is a significant factor to reach a drug development. Hence, protein kinases play an important role in drug designing (e.g, LmxMPK and CRK3). This study is developed to predict and assess the three-dimensional structure for E9BJT5 protein in Leishmania and its binding affinity for different calcium channel blockers. Materials & Methods: The three-dimensional structure was predicted and assessed for the protein by the I-TASSER and Procheck servers, respectively. In the molecular docking method, interactions between different calcium channel blockers and the predicted model of E9BJT5 were investigated using the Autodock vina in PyRx 0.8 software. Thereafter, the interaction results were analyzed by Chimera software, and thus the stronger potential interactions were identified. Results: Docking results showed that the lidoflazine and lercanidipine (the values were -8.3 and -7.6 kcal/mol, respectively) were obtained as the top-ranked drugs in the binding to the active site of the protein. Conclusion: In this study, using in silico approach, the E9BJT5 protein could be a viable target for designing the novel drugs against the Leishmania parasite. The docking results demonstrated that two drugs (i.e., lidoplasin and lercantipine) may be considered as anti-leishmanial drugs. Further studies are recommended to evaluate the interactions between these drugs and the target.